Ownership Structure Of The Capital Market Earning Management Model: A Meta-Analysis Study - Surayya SURAYYA; Djayani NURDIN; Muhamad Yunus KASIM; Muslimin MUSLIMIN; Juliana KADANG (Journal of Tourism Economics and Policy, 2023)
The purpose of this study is to identify and analyze (1) the ownership structure, which consists of institutional ownership, managerial ownership, and ownership concentration on earning management in the capital market; (2) the Jones Model and Modified Jones Model's moderation of the ownership structure of earnings management in the capital market. This study used a population of 40 research from various articles and as many as 26 articles that passed the selection of data used in research with various criteria. Data analysis techniques use meta-analysis to measure each variable in this study. The results show that institutional ownership does not affect earning management in the capital market. Managerial ownership and concentration of ownership significantly affect earning management in the capital market. Earning management models such as the Jones Model and Modified Jones Model do not moderate the ownership structure, namely institutional ownership, managerial ownership and ownership concentration on earning management in the capital market.